2021
DOI: 10.3389/fchem.2021.777041
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrin Photoabsorption and Fluorescence Variation with Adsorptive Loading on Gold Nanoparticles

Abstract: Here, we report the photophysical structure–property relationship of porphyrins adsorbed on gold nanoparticles. The number of porphyrin–alkanethiolate adsorbates per particle was adjusted by a post-synthetic thiol/thiolate exchange reaction on 1-dodecanethiolate–protected gold nanoparticles. Even with a low loading level of adsorbates (<10% of all thiolate sites on gold nanoparticles), the shoulder absorption at the Soret band was intensified, indicating the formation of aggregates of porphyrin adsorbat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
(75 reference statements)
0
0
0
Order By: Relevance
“…We have previously shown that a gold nanoparticle (AuNP) efficiently quenches the excited state of porphyrin when they are covalently linked to form a conjugate [16][17][18]. In the porphyrin-AuNP conjugates [16], 1 O 2 generation was almost quenched (singlet oxygen generation quantum yield, Φ ∆ = 0.01−0.08) from corresponding unbound porphyrin (Φ ∆ = 0.70 for meso-tetraphenyl porphyrin (TPP) [19], at a partial pressure of oxygen pO 2 = 0.21 atm).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that a gold nanoparticle (AuNP) efficiently quenches the excited state of porphyrin when they are covalently linked to form a conjugate [16][17][18]. In the porphyrin-AuNP conjugates [16], 1 O 2 generation was almost quenched (singlet oxygen generation quantum yield, Φ ∆ = 0.01−0.08) from corresponding unbound porphyrin (Φ ∆ = 0.70 for meso-tetraphenyl porphyrin (TPP) [19], at a partial pressure of oxygen pO 2 = 0.21 atm).…”
Section: Introductionmentioning
confidence: 99%